A Multicast Algorithm for Wireless Sensor Networks Based on Network Coding. (20th January 2014) - Han, Zhi-jie; Wang, Ru-chuan; Xiao, Fu
Abstract : We propose a set of distributed algorithms for improving the multicast throughput in wireless sensor networks. To this end, network coding is applied when exploiting path diversity with two disjoint paths to each multicast group receiver. We depart from the traditional wisdom that the multicast topology from source to receivers needs to be a tree and propose a novel and distributed algorithm to construct a 2-redundant multicast graph (a directed acyclic graph) as the multicast topology, on which network coding is applied. We conduct both analytical and simulation-based studies to evaluate the effectiveness and performance of our algorithm.